2022
DOI: 10.1371/journal.pone.0265397
|View full text |Cite
|
Sign up to set email alerts
|

The syndemic effects of adverse mental health conditions and polysubstance use on being at risk of clinical depression among marginally housed and homeless transitional age youth living in San Francisco, California

Abstract: The objective of this study was to identify the correlates of being at risk of clinical depression and examine the role of syndemic factors among marginally housed and homeless transitional age youth (TAY). From 2017–2018, 100 TAY between the ages of 18 and 24 in San Francisco were recruited from Larkin Street Youth Services into a cross-sectional study. Participants completed surveys on mental health, substance use, and HIV risk behaviors. A syndemic score ranging from 0–3 was calculated by summing dichotomou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Los resultados de esta investigación han resaltado, por un lado, temas clave como la sobrerrepresentación de las PSH LGBT+ (Dempsey et al, 2020;Fraser et al, 2019;Tyler y Schmitz, 2018) mostrando que el principal motivo, es el rechazo familiar después de revelar la orientación sexual e identidad de género (Castellanos, 2016), afectando en mayor medida a las personas trans y mujer trans (Gimenez et al, 2019). También se han señalado los numerosos problemas de salud, enfermedades mentales, suicidios e intentos de suicidios y abuso de sustancias entre dicha población (Jain et al, 2022;Santa María et al, 2020;Moskowitz et al, 2013). Por otro lado, existen áreas que requieren una mayor consideración y atención.…”
Section: Discussionunclassified
“…Los resultados de esta investigación han resaltado, por un lado, temas clave como la sobrerrepresentación de las PSH LGBT+ (Dempsey et al, 2020;Fraser et al, 2019;Tyler y Schmitz, 2018) mostrando que el principal motivo, es el rechazo familiar después de revelar la orientación sexual e identidad de género (Castellanos, 2016), afectando en mayor medida a las personas trans y mujer trans (Gimenez et al, 2019). También se han señalado los numerosos problemas de salud, enfermedades mentales, suicidios e intentos de suicidios y abuso de sustancias entre dicha población (Jain et al, 2022;Santa María et al, 2020;Moskowitz et al, 2013). Por otro lado, existen áreas que requieren una mayor consideración y atención.…”
Section: Discussionunclassified
“…Likewise, harmful social conditions such as poverty are often associated with food insecurity, homelessness, and comorbidities that make HIV treatment challenging to maintain (Garcia & Kushel, 2022;Tang et al, 2011). In a nutshell, rather than individual risk factors, these findings suggest the existence of patterns of correlated risk factors like the ones proposed in syndemic theory and the literature on multimorbidity (Freedland et al, 2021;Jain et al, 2022;Strathdee et al, 2013). We define syndemics in HIV as the synergistic epidemics of substance use, violence, diminished psychological well-being, and HIV among impacted populations, particularly those burdened by socioeconomic disadvantages (Sheehan et al, 2020;Tsai, 2018;Tsai & Burns, 2015).…”
mentioning
confidence: 94%
“…With the concept of syndemics well applied to HIV research, such as the SAVA syndemic [14], more attention is being paid to its role in mental health. One study on youth in California [15] found that the syndemic effects of multiple adverse mental health conditions significantly increased the risk of depression. Another survey in the U.S. noted the syndemic effects of recent maltreatment including emotional maltreatment, neglect, and witnessing family violence on young people's suicidal or self-harm ideation [16].…”
Section: Introductionmentioning
confidence: 99%